PENGARUH DISKON DAN INFLUENCER TERHADAP KEPUTUSAN PEMBELIAN PRODUK VIRTUAL PADA PLAYER MOBILE LEGENDS DI SURABAYA - Verdynata, Ega; Pratiwi, MM, Dra. Ni Made Ida; Maduwinarti, MP, Dr. Dra. Ayun; Maduwinarti, MP, Dr. Dra. Ayun (Research Journal of Social Science and Economics, 2025)
Along with technological developments it has an impact on the entertainment industry, including game technology. Games that were originally only played alone can now be connected with other players using internet technology to play games online. One of the popular online games today is Mobile Legends which is a multiplayer game published by Moonton in which two teams compete against each other. In this game there are virtual products that can be purchased to enhance the playing experience. Mobile Legends which is a new game but can generate large revenues and continues to increase every year even though they offer many types of virtual products and continue to provide the latest products. This study will further analyze the effect of discounts and influencers on purchasing decisions for virtual products for Mobile Legends players in Surabaya. This study uses a quantitative method by distributing e-questions via Google Form to Mobile Legends players in Surabaya. This study used a purposive sampling method and determined 100 respondents. The collected data were analyzed using multiple linear regression methods to examine the relationship between discount, influencer, and virtual product purchasing decisions. The results of the study show that discounts have a significant effect on virtual product purchasing decisions. The bigger the discount offered, the higher the probability that players will buy the virtual product. Then influencers have a significant influence on purchasing decisions for virtual products. Mobile Legends players tend to be interested in buying virtual products recommended by influencers.